THE EFFECT OF CHALLENGE STRESSORS AND JOB DEMAND ON CREATIVITY: THE MEDIATION ROLE OF JOB BURNOUT - Mgs Muhamad Ilham Rafiansyah; Handrio Adhi Pradana (JPIM (Jurnal Penelitian Ilmu Manajemen), 2022)
This study aims to examine influence of Challenge Stressors and Job Demand on Creativity mediated by Job Burnout. This research was conducted quantitatively with 135 respondents consisting of online transportation drivers from Go-Jek, Grab, Shopee-Food, Maxim spread across Palembang, Bekasi, Madiun, Pontianak, and Yogyakarta. Sampling using analysis using purposive sampling method. This research was conducted using the SPSS version 25 application to address multiple regression analysis. The data analysis method use SOBEL technique to test the mediating. Results indicate that Challenge Stressors and Job Demand have positive and significant effect on Creativity and Job Burnout. In addition, Job Burnout influences negative and significant toward Creativity. Finally, Job Burnout mediates Challenge Stressors and Job Demand on the relationship of both variables toward Creativity.